AD7c-NTP Impairs Adult Striatal Neurogenesis by Affecting the Biological Function of MeCP2 in APP/PSl Transgenic Mouse Model of Alzheimer's Disease - Li, Pan; Quan, Wei; Wang, Zengguang; Chen, Yuan; Zhang, Huihong; Zhou, Yuying (Frontiers in Aging Neuroscience, 2021)
The processes by which neural stem cells (NSCs) and neural precursor cells (NPCs) transform into the characteristic lineages observed in Alzheimer disease (AD) are poorly characterized. Understanding these processes if of critical importance due to the increased prevalence of AD and the lack of effective AD strategies. Here, we used immunohistochemistry and western blot to find that MeCP2 was phosphorylated at a specific amino acid residue, Serine 421 (S421) and activated in response to AD induced damage in APP/PSl transgenic mice , altering its nuclear to cytoplasmic shuttling. Epigenetic examinations combined with Chromatin immunoprecipitation and Methylated DNA immunoprecipitation revealed that the translocation of MeCP2 from nucleus to cytoplasm led to the loss of lineage specific gene promoters (such as Gfap, Nestin and Dcx), decreased transcriptional repression and the activation of gene expression. Immunofluorescence data demonstrated that neurogenic progenitors with high levels of active phosphorylated MeCP2 at S421 (MeCP2 pS421) possessed a high probability of development into DCX-expressing cells. AD7c-NTP will control neurogenic progenitor regeneration through its effects on MeCP2 pS421 leading to altered lineage specific gene expression. This adds to the growing list of biological effects of AD7c-NTP in the brain and highlights MeCP2 as relevant to the plasticity of neural cells in the AD mice striatum.